Internet competency predicts practical hearing aid knowledge and skills in first-time hearing aid users - Maidment, David W.; Brassington, William; Wharrad, Heather; Ferguson, Melanie A. (ASHA, 2016)
Purpose. The purpose of the study was to assess whether Internet competency predicted practical hearing aid knowledge and handling skills in first-time hearing aid users.